2008
DOI: 10.1073/pnas.0805420105
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α2β1 plays a critical role in osteoblast response to micron-scale surface structure and surface energy of titanium substrates

Abstract: Efforts to improve bone response to biomaterials have focused on ligands that bind ␣5␤1 integrins. However, antibodies to ␣5␤1 reduce osteoblast proliferation but do not affect differentiation when cells are grown on titanium (Ti). ␤1-silencing blocks the differentiation stimulus of Ti microtopography, suggesting that other ␤1 partners are important. Stably ␣2-silenced MG63 human osteoblast-like cells were used to test whether ␣2␤1 specifically mediates osteoblast response to Ti surface micron-scale structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(209 citation statements)
references
References 62 publications
17
182
0
7
Order By: Relevance
“…Finally, the difference will affect the regulation of cell adhesion, motility, proliferation, and differentiation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the difference will affect the regulation of cell adhesion, motility, proliferation, and differentiation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…As integrins are receptor molecules for extracellular matrix molecules (e.g., the β 1 family), serum components (α v family) and immunoglobulin family adhesion molecules (β 2 family), these molecules are obviously critical in cell behaviour. Previous studies have identifi ed that integrin β 1 is required for osteoblastic differentiation on microscale Ti substrates (Olivares-Navarrete et al, 2008;Chuluyan et al, 1995). β 1 integrin recognises that the VCAM-1 counter receptor presents on endothelial cells and ECM proteins such as fibronectin, collagen and vitronectin (Issekutz, 1995;Meerschaert and Furie 1995;Lai et al, 2000).…”
Section: Wwwecmjournalorg S Lavenus Et Al Mesenchymal Stem Cells Omentioning
confidence: 99%
“…Using an image analysis and PCR array, we show the infl uence of pore diameter on hMSC adhesion. Previous studies have shown that changes in cell shape or integrin expression could regulate commitment of mesenchymal cells to different lineage (Olivares-Navarrete et al, 2008;Lavenus et al, 2011). Hence, the osteogenic differentiation of hMSCs on the nanostructured Ti was compared with Ti planar substrates with or without osteogenic supplements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that on rough surfaces osteoblasts exhibit a more differentiated phenotype, even though the proliferation is negatively affected. The mechanism by which topography influences osteoblast differentiation appears to be mediated by integrin signaling (Olivares-Navarrete et al, 2008) and mitogen-activated proteine kinase (MAPK) pathways (Schwartz et al, 2001b). The topography has also an effect on subsequent expression of transcription factors, ECM protein genes and cytokines (Balloni et al, 2009;Marinucci et al, 2006).…”
Section: Topographical Features Of Titanium Surfacesmentioning
confidence: 99%